2009
DOI: 10.1159/000235731
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Captopril and Allopurinol Retards Fructose-Induced Metabolic Syndrome

Abstract: Background: Both ACE inhibitors and allopurinol have been shown to partially prevent metabolic syndrome induced by fructose. We tested the hypothesis that combined therapy might be more effective at blocking the metabolic syndrome induced with fructose. Methods: Male Sprague-Dawley rats were fed a high fructose diet with or without allopurinol, captopril, or the combination for 20 weeks. A control group received a normal diet. All groups were pair-fed to assure equivalent caloric intake. Results: Despite reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 81 publications
7
31
0
1
Order By: Relevance
“…This could be attributed to the effect of sodium nitrate in inducing nitric oxide-like bioactivity in humans including a robust reduction in blood pressure, inhibition of platelet aggregation and improvement of endothelial function [15,20,33]. On the other hand, and in accordance with our study, it was found that allopurinol had a partial effect in preventing the rise Comparing the effects of inorganic nitrate and allopurinol in renovascular complications of metabolic syndrome in rats: role of nitric oxide and uric acid in arterial blood pressure when compared to captopril, a potent antihypertensive drug [22]. However, allopurinol was a potent drug in reducing both the hyperuricemia and the increase in the adipose tissue index induced by the metabolic syndrome compared to the effect of sodium nitrate.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This could be attributed to the effect of sodium nitrate in inducing nitric oxide-like bioactivity in humans including a robust reduction in blood pressure, inhibition of platelet aggregation and improvement of endothelial function [15,20,33]. On the other hand, and in accordance with our study, it was found that allopurinol had a partial effect in preventing the rise Comparing the effects of inorganic nitrate and allopurinol in renovascular complications of metabolic syndrome in rats: role of nitric oxide and uric acid in arterial blood pressure when compared to captopril, a potent antihypertensive drug [22]. However, allopurinol was a potent drug in reducing both the hyperuricemia and the increase in the adipose tissue index induced by the metabolic syndrome compared to the effect of sodium nitrate.…”
Section: Discussionsupporting
confidence: 89%
“…Features of the syndrome were in the form of hypertension, hyperuricemia and hyperinsulinemia in accordance with Roncal et al [22].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Experimental studies have also documented that fructose is distinct from glucose in its ability to induce metabolic syndrome and that this is independent of energy intake. 5,6 These data are consistent with a recent meta-analysis that found that high-fructose corn syrup-containing beverages increase the risk for metabolic syndrome and diabetes. 7 Our finding that we induced metabolic syndrome in 25% of adults within 2 weeks is of great concern.…”
Section: Conflict Of Interestsupporting
confidence: 87%
“…34 Extension of HFD feeding to 12 (J.Y.H. Chan et al, unpublished data, 2014) or 20 weeks 47 also did not cause a significant increase in body weight. We therefore reason that it is unlikely that the relationship between oxidative stress in RVLM and development of hypertension in this HFD model of MetS is obesity-dependent.…”
Section: Discussionmentioning
confidence: 92%